Effect of Type 1 Diabetes on School Performance in a Dynamic World: New Analysis Exploring Swedish Register Data - Emma Persson; Sofie Persson; Ulf-G. Gerdtham; Katarina Steen Carlsson (Lund University, School of Economics and Management, Department of Economics, 2016)
This paper investigates if the effect of type 1 diabetes mellitus (T1DM) on school performance has changed over time using national Swedish population register data. The issue is of interest because management and treatment of the disease have improved over the last decades and, furthermore, because of changes in the educational grading system. Despite these changes, data indicate a persistent negative effect of T1DM on compulsory and upper secondary school grades and the results appears similar to earlier findings on cohorts completing school under the previous grading system. Moreover, the results are robust to alternative model specifications and econometric estimation strategies. Whereas access to new treatment technologies and improved diabetes management strategies has reduced the burden of diabetes in daily life, the results from this study indicate that other trends have not implied a reduction, over time, in the impact of T1DM on school performance. This finding indicates that continued efforts are needed to improve the situation in school for children with T1DM to prevent potential long-term socioeconomic consequences.
Keywords: I00; I10; I21; J24; 330; type 1 diabetes; education; school performance; register data